The Natural History Society of Montreal's Museum and the Socio-Economic Significance of Museums in 19th-Century Canada - Gagnon, Hervé (Scientia Canadensis, 1994)
ABSTRACTThe Natural History Society of Montreal's Museum, the first science museum in Montreal, was led, throughout the first half of the 19th century, by members of the local anglophone bourgeoisie. It temporarily prospered with the increased involvement of the Geological Survey of Canada with the Society during the 1850s and 1860s, until the economic crisis of the 1870s and the departure of the Survey for Ottawa in 1881 restored it to its amateur status.